Hubungan Komunikasi dengan Prestasi Atlet - Fandu Faisal; Zulham Zulham; Abdul Syukur; Dini Safitri (Communicatus: Jurnal Ilmu komunikasi, 2018)
This study aims to explain the relationship of communication with the achievements of badminton athletes SMP 116 Ragunan, on Djarum Sirnas championship, 2017. Many examples of cases, athletes who have not realized that they have more ability in himself, becomes an interesting problem to be examined and whether it has something to do with communication between athlete and coach? Researchers use the theory communication, especially about the factors that influence the formation of communication, to be able to explore the process of interpersonal communication between athletes and trainers. The methodology of this research is quantitative. The results showed that there was a relationship between coach communication, both in verbal and nonverbal communication with athlete achievement. The communication skills of the coach in building or creating shared, open, and shared communication messages of content (athletes with trainers) have a stronger relationship than the other 3 dimensions, namely the dimension of collaboration, the dimension of critical thinking, and the dimensions of creativity.Penelitian ini bertujuan untuk menjelaskan hubungan komunikasi dengan prestasi atlet bulutangkis SMP 116 Ragunan, pada kejuaran Djarum Sirnas, 2017. Banyak contoh kasus, atlet yang belum menyadari bahwa mereka memiliki kemampuan lebih di dalam dirinya, menjadi masalah menarik untuk diteliti dan apakah hal tersebut ada hubungannya dengan komunikasi antara atlet dengan pelatih? Peneliti menggunakan teori komunikasi, khususnya mengenai faktor-faktor yang mempengaruhi terbentuknya komunikasi, untuk dapat mengeksplorasi proses komunikasi interpersonal antara atlet dan pelatih. Metodologi penelitian ini adalah kuantitatif. Hasil penelitian menunjukan bahwa terdapat hubungan antara komunikasi pelatih, baik dalam komunikasi verbal dan nonverbal dengan prestasi atlet. Kemampuan komunikasi pelatih dalam membangun atau menciptakan pesan-pesan komunikasi (content) yang bersifat berbagi pemikiran, terbuka, dan mencakup solusi untuk kepentingan bersama (atlet dengan pelatih) memiliki hubungan yang lebih kuat dibanding 3 dimensi lainnya, yaitu dimensi collaboration, dimensi critical thinking, dan dimensi creativity.